2008
DOI: 10.1073/pnas.0802465105
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for IL-13 and IL-4 via IL-13 receptor α1 and the type II IL-4 receptor in asthma pathogenesis

Abstract: inflammation ͉ cytokines ͉ eosinophils ͉ chemokines ͉ mucus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
253
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(276 citation statements)
references
References 32 publications
17
253
0
2
Order By: Relevance
“…A reason for that may be both cytokines competitively bind to the type II IL-4R receptor that was completely saturated at the concentrations used. Overall, IL-4 had a bigger effect on the CBF than IL-13, possibly because IL-4 additionally binds to the type I IL-4R receptor whereas IL-13 does not (20,24,25). The table shows the mean CBF with sD within the different experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A reason for that may be both cytokines competitively bind to the type II IL-4R receptor that was completely saturated at the concentrations used. Overall, IL-4 had a bigger effect on the CBF than IL-13, possibly because IL-4 additionally binds to the type I IL-4R receptor whereas IL-13 does not (20,24,25). The table shows the mean CBF with sD within the different experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ/Ϫ , and Il13ra2 Ϫ/Ϫ mice (N10 BALB/c) were bred at Cincinnati Children's Hospital Medical Center as described previously (20). All mice were maintained in a barrier facility, and animals were handled under Cincinnati Children's Hospital Medical Center and IACUC-approved protocols.…”
Section: Methodsmentioning
confidence: 99%
“…As a cause of airway inflammation and asthma, IL-4 has been considered to be the best therapeutic target in asthma. However, several clinical and fundamental studies have demonstrated that IL-9 and IL-13 are more important cytokines in the onset of allergic asthma than IL-4 (13,(42)(43)(44). Moreover, it was also demonstrated that IL-9 induces IL-13 expression in airway epithelial cells and promotes airway inflammation (45).…”
Section: Discussionmentioning
confidence: 99%